The Attitudes of Students from ESL and EFL Countries to English - Muhamad Hasbi (Register Journal, 2013)
This research is to study the attitudes of English students from English as a Second Language (ESL) and English as a Foreign Language (EFL) country in English and Foreign Languages University (EFL University), Hyderabad to English. This is a descriptive-quantitative research with a survey method. The attitudes researched include those to listening, speaking, reading, and writing. The data was taken through questionnaire consisting of 20 questions. The findings of this study showed that the English students in EFL University have neutral-to-positive attitudes to Listening, positive attitudes to Speaking, positive attitudes to Reading, and poor attitudes to Writing. In addition, the English students from ESL country have better attitudes to Reading (positive) and Writing (neutral) and those from EFL country have better attitudes to Speaking (neutral-to-positive) and Listening (neutral-to-positive).